1996
DOI: 10.1074/jbc.271.18.10672
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of 92-kDa Gelatinase B Promoter Activity by ras Is Mitogen-activated Protein Kinase Kinase 1-independent and Requires Multiple Transcription Factor Binding Sites Including Closely Spaced PEA3/ets and AP-1 Sequences

Abstract: The 92-kDa type IV collagenase (92-kDa gelatinase B also referred to as MMP-9), which plays a critical role in extracellular matrix degradation, is regulated by growth factors that mediate their effects through the ras proto-oncogene. The current study was undertaken to determine the transcriptional requirements for the induction of 92-kDa gelatinase B expression by an activated ras oncogene. Transfection of OVCAR-3 cells with an expression vector encoding an activated Ha-ras increased 92-kDa gelatinolytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
246
4

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 332 publications
(262 citation statements)
references
References 50 publications
12
246
4
Order By: Relevance
“…Mutation of either TRE-1 or TRE-2 also reduced promoter function. Similar to the data previously shown for both src and ras activation of the MMP-9 gene, disruption of the RBE abrogated promoter function (Gum et al, 1996;. Finally, replacement of the CA dinucleotide repeat sequence in the downstream promoter also markedly reduced reporter expression.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Mutation of either TRE-1 or TRE-2 also reduced promoter function. Similar to the data previously shown for both src and ras activation of the MMP-9 gene, disruption of the RBE abrogated promoter function (Gum et al, 1996;. Finally, replacement of the CA dinucleotide repeat sequence in the downstream promoter also markedly reduced reporter expression.…”
supporting
confidence: 82%
“…Coordinate activation of the NFkB, SP-1, and most proximal TRE-1 were required for promoter activation by tumor necrosis factor-a (TNF-a) or by phorbol ester (TPA), while the RBE and most proximal TRE-1 appeared to be su cient for transcriptional activation by the src oncogene . Gum et al showed that several transcription factor binding sites, including the adjoining upstream Ets and TRE-2 sites, were necessary for MMP-9 upregulation mediated by the ras oncogene (Gum et al, 1996).…”
mentioning
confidence: 99%
“…Induction of MMP-9 promoter activity by oncogenic Ras in squamous carcinoma cells has been shown to be abrogated by blocking the ERK 1/2 pathway (Gum et al, 1997). Increased transcriptional activity of the MMP-9 promoter in Ras-transformed ovarian carcinoma cells has also been shown to be mediated by MAP kinases (Gum et al, 1996). In the present study, we show that down-regulation of constitutive b6 expression using an antisense approach against b6, that is known to suppress MAP kinase activity (Ahmed et al, 2002), dramatically reduced MMP-9 levels in tumour-conditioned medium.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Thus, previous reports suggest that the ets family may activate the transcription of genes encoding collagenase 1, stromelysine 1 and urokinase plasminogen activator, which are proteases involved in extracellular matrix degradation. [25][26][27] It is believed that the ets family takes part in regulating angiogenesis by controlling the transcription of these genes whose activity is necessary for the migration of endothelial cells from pre-existing capillaries. In this study, we also demonstrated the up-regulation of endogenous HGF expression by exogenously transfected HGF gene, consistent with our previous findings in in vitro experiments.…”
Section: Figure 3 Effect Of the Transfection Of Hgf Vector On The Vasmentioning
confidence: 99%